The sound sensation of apical electric stimulation in cochlear implant recipients with contralateral residual hearing. - Diane S Lazard; Jeremy Marozeau; Hugh J McDermott (PLoS ONE, 2012)
BACKGROUND: Studies using vocoders as acoustic simulators of cochlear implants have generally focused on simulation of speech understanding, gender recognition, or music appreciation. The aim of the present experiment was to study the auditory sensation perceived by cochlear implant (CI) recipients with steady electrical stimulation on the most-apical electrode. METHODOLOGY/PRINCIPAL FINDINGS: Five unilateral CI users with contralateral residual hearing were asked to vary the parameters of an acoustic signal played to the non-implanted ear, in order to match its sensation to that of the electric stimulus. They also provided a rating of similarity between each acoustic sound they selected and the electric stimulus. On average across subjects, the sound rated as most similar was a complex signal with a concentration of energy around 523 Hz. This sound was inharmonic in 3 out of 5 subjects with a moderate, progressive increase in the spacing between the frequency components. CONCLUSIONS/SIGNIFICANCE: For these subjects, the sound sensation created by steady electric stimulation on the most-apical electrode was neither a white noise nor a pure tone, but a complex signal with a progressive increase in the spacing between the frequency components in 3 out of 5 subjects. Knowing whether the inharmonic nature of the sound was related to the fact that the non-implanted ear was impaired has to be explored in single-sided deafened patients with a contralateral CI. These results may be used in the future to better understand peripheral and central auditory processing in relation to cochlear implants.